Intestinal microbiota-derived tryptophan metabolites are predictive of Ah receptor activity. Issue 1 (9th November 2020) - Dong, Fangcong; Hao, Fuhua; Murray, Iain A.; Smith, Philip B.; Koo, Imhoi; Tindall, Alyssa M.; Kris-Etherton, Penny M.; Gowda, Krishne; Amin, Shantu G.; Patterson, Andrew D.; Perdew, Gary H.
ABSTRACT: Commensal microbiota-dependent tryptophan catabolism within the gastrointestinal tract is known to exert profound effects upon host physiology, including the maintenance of epithelial barrier and immune function. A number of abundant microbiota-derived tryptophan metabolites exhibit activation potential for the aryl hydrocarbon receptor (AHR). Gene expression facilitated by AHR activation through the presence of dietary or microbiota-generated metabolites can influence gastrointestinal homeostasis and confer protection from intestinal challenges. Utilizing untargeted mass spectrometry-based metabolomics profiling, combined with AHR activity screening assays, we identify four previously unrecognized tryptophan metabolites, present in mouse cecal contents and human stool, with the capacity to activate AHR. Using GC/MS and LC/MS platforms, quantification of these novel AHR activators, along with previously established AHR-activating tryptophan metabolites, was achieved, providing a relative order of abundance. Using physiologically relevant concentrations and quantitative gene expression analyses, the relative efficacy of these tryptophan metabolites with regard to mouse or human AHR activation potential is examined. These data reveal indole, 2-oxindole, indole-3-acetic acid and kynurenic acid as the dominant AHR activators in mouse cecal contents and human stool from participants on a controlled diet. Here we provide the first documentation of the relative abundance and AHR activation potential of a panel of microbiota-derived tryptophan metabolites. Furthermore, these data reveal the human AHR to be more sensitive, at physiologically relevant concentrations, to tryptophan metabolite activation than mouse AHR. Additionally, correlation analyses indicate a relationship linking major tryptophan metabolite abundance with AHR activity, suggesting these cecal/fecal metabolites represent biomarkers of intestinal AHR activity.